2012
DOI: 10.1016/j.compstruct.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Flexural performance of FRP reinforced concrete beams

Abstract: A numerical method for estimating the curvature, deflection and moment capacity of FRP reinforced concrete beams is developed. Force equilibrium and strain compatibility equations for a beam section divided into a number of segments are numerically solved due to the nonlinear behaviour of concrete. The deflection is then obtained from the flexural rigidity at midspan section using the deflection formaule for various load cases. A proposed modification to the mid-span flexural rigidity is also introduced to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 18 publications
0
33
0
3
Order By: Relevance
“…This result seems to corroborate with that of Kassem et al [26] findings wherein they found out that increasing ρf by 50% and 100% will marginally increase the flexural capacity by just 4% and 16 %, respectively. The study conducted by Kara et al [44] showed that, for over-reinforced FRP-reinforced concrete beams, a large increase in FRP reinforcement produced a modest increase in normalised capacity. El-Nemr et al [6], however, suggested that the influence of ρf on the strength of FRP-reinforced concrete beams could be fully realised when ρf is increased three to four times.…”
Section: Influence Of the Reinforcement Ratiomentioning
confidence: 99%
“…This result seems to corroborate with that of Kassem et al [26] findings wherein they found out that increasing ρf by 50% and 100% will marginally increase the flexural capacity by just 4% and 16 %, respectively. The study conducted by Kara et al [44] showed that, for over-reinforced FRP-reinforced concrete beams, a large increase in FRP reinforcement produced a modest increase in normalised capacity. El-Nemr et al [6], however, suggested that the influence of ρf on the strength of FRP-reinforced concrete beams could be fully realised when ρf is increased three to four times.…”
Section: Influence Of the Reinforcement Ratiomentioning
confidence: 99%
“…In the present study, moment-curvature relationships of FRP and steel reinforced concrete beams have been obtained by the numerical technique developed by Kara and Ashour [20] as summarized below. The moment-curvature relationships predicted are compared with these from experimental results for FRP and steel reinforced concrete beams.…”
Section: Moment-curvature Relationship Of Reinforced Concrete Sectionsmentioning
confidence: 99%
“…Recently, there has been extensive research to investigate the flexural behavior of FRP reinforced concrete members [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Many design approaches to calculate the deflection of FRP reinforced concrete members have been proposed in these studies.…”
Section: Introductionmentioning
confidence: 99%